1995
DOI: 10.1103/physrevc.51.3343
|View full text |Cite
|
Sign up to set email alerts
|

Azimuthal correlations of pions in relativistic heavy-ion collisions at 1 GeV/nucleon

Abstract: Triple differential cross sections of pions in heavy ion collisions at 1 GeV/nucl. are studied with the IQMD model. After discussing general properties of ∆ resonance and pion production we focus on azimuthal correlations: At projectile-and target-rapidities we observe an anticorrelation in the in-plane transverse momentum between pions and protons. At c.m.-rapidity, however, we find that high p t pions are being preferentially emitted perpendicular to the event-plane. We investigate the causes of those correl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
150
4

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(162 citation statements)
references
References 78 publications
8
150
4
Order By: Relevance
“…The anti-correlation of nucleons and pions was explained in Ref. [50] as due to an effect of multiple πN scattering. However, in Ref.…”
Section: Directed Flow Of π − -Mesonsmentioning
confidence: 99%
“…The anti-correlation of nucleons and pions was explained in Ref. [50] as due to an effect of multiple πN scattering. However, in Ref.…”
Section: Directed Flow Of π − -Mesonsmentioning
confidence: 99%
“…However, pions from the more dilute large-|z| region have less opportunity for rescattering and so retain the positive p x −p z correlation of their (flowing) parent ∆'s. Similar considerations generate a sign change in the pion flow as the impact parameter is varied in transport models [18].…”
mentioning
confidence: 99%
“…This bears directly on the physical causes of directed pion flow at these energies. Detailed transport model studies [18] have shown that pion reflection from (not absorption by) the nucleonic matter is at the root of directed pion flow at these energies. Focussing on the forward hemisphere, if absorption processes (πN N → ∆N → N N ) were dominant in producing pion flow, we would expect an absence of π emission points in the +x quadrant, i.e.…”
mentioning
confidence: 99%
“…5, the spectrum of invariant cross-sections of ∆ 0 (1232)-resonances, produced in p+ 12 C collisions, is fitted well by the function in Eq. (16) (17) and (18) with two and three slopes respectively are shown for rapidity intervals −0 4 < < 1 1 and −0 4 < < 2 2. The corresponding parameters of approximation of ( ) by functions in expressions (17) and (18) are presented in Tab.…”
mentioning
confidence: 99%